Standardized enhanced adherence counseling for improved HIV viral suppression among children and adolescents in Homa Bay and Turkana Counties, Kenya. Issue 40 (7th October 2022) - Masaba, Rose Otieno; Woelk, Godfrey; Herrera, Nicole; Siamba, Stephen; Simiyu, Rogers; Ochanda, Boniface; Okomo, Gordon; Odionyi, Justine; Audo, Michael; Mwangi, Eliud
Abstract : Viral suppression is suboptimal among children and adolescents on antiretroviral therapy (ART) in Kenya. We implemented and evaluated a standardized enhanced adherence counseling (SEAC) package to improve viral suppression in children and adolescents with suspected treatment failure in Homa Bay and Turkana. The SEAC package, implemented from February 2019 to September 2020, included: standard procedures operationalizing the enhanced adherence counseling (EAC) process; provider training on psychosocial support and communication skills for children living with HIV and their caregivers; mentorship to providers and peer educators on EAC processes; and individualized case management. We enrolled children and adolescents aged 0 to 19 years with suspected treatment failure (viral load [VL] >1000 copies/mL) who received EAC before standardization as well as those who received SEAC in a pre-post evaluation of the SEAC package conducted in 6 high-volume facilities. Pre-post standardization comparisons were performed using Wilcoxon-Mann-Whitney and Pearson's chi-square tests at a 5% level of significance. Multivariate logistic regression was performed to identify factors associated with viral resuppression. The study enrolled 741 participants, 595 pre- and 146 post-SEAC implementation. All post-SEAC participants attended at least 1 EAC session, while 17% (n = 98) of pre-SEAC clients had no record of EAC attendance. Time to EAC following the detection of high VL was reduced by a median of 8 days, from 49 (interquartile range [IQR]: 23.0–102.5) to 41 (IQR: 20.0–67.0) days pre- versus post-SEAC ( P  = .006). Time to completion of at least 3 sessions was reduced by a median of 12 days, from 59.0 (IQR: 36.0–91.0) to 47.5 (IQR: 33.0–63.0) days pre- versus post-SEAC ( P  = .002). A greater percentage of clients completed the recommended minimum 3 EAC sessions at post-SEAC, 88.4% (n = 129) versus 61.1% (n = 363) pre-SEAC, P  < .001. Among participants with a repeat VL within 3 months following the high VL, SEAC increased viral suppression from 34.6% (n = 76) to 52.5% (n = 45), P  = .004. Implementation of the SEAC package significantly reduced the time to initiate EAC and time to completion of at least 3 EAC sessions, and was significantly associated with viral suppression in children and adolescents with suspected treatment failure.